The applications of graphene-based materials in pollutant control and disinfection. (March 2017) - Tsang, Chi Him A.; Kwok, H.Y.H.; Cheng, Zhanjun; Leung, D.Y.C.
Abstract: Due to their extra-large surface area and porosity, high compression power, hydrophobicity, and strong activity characteristics, there have been increasing interests in applying graphene-based materials for pollutant control and disinfection. The topics covered from photocatalytic reactions in the dye removal and organic conversions in liquid or gas phase, disinfection, oil absorption, and pollutant adsorption. In this manuscript, the characteristics of the photocatalytic reactions for toxins and pollutants like toxic hydrocarbons, carbon dioxides, and dye wastewater, removal of pollutants like oil and heavy metal ions via absorption/adsorption, and disinfection by different graphene-based materials via adsorption inactivation or photocatalytic inactivation will be emphasized. The challenges in pollutant removal research by graphene-based materials, such as the deactivation of graphene-based materials in photocatalytic pollutant removal reactions which was discovered recently and solutions to the corresponding weaknesses were discussed.